Fast and Highly Sensitive Ionic‐Polymer‐Gated WS2–Graphene Photodetectors. Issue 23 (18th April 2017) - Mehew, Jake D.; Unal, Selim; Torres Alonso, Elias; Jones, Gareth F.; Fadhil Ramadhan, Saad; Craciun, Monica F.; Russo, Saverio
Abstract : The combination of graphene with semiconductor materials in heterostructure photodetectors enables amplified detection of femtowatt light signals using micrometer‐scale electronic devices. Presently, long‐lived charge traps limit the speed of such detectors, and impractical strategies, e.g., the use of large gate‐voltage pulses, have been employed to achieve bandwidths suitable for applications such as video‐frame‐rate imaging. Here, atomically thin graphene–WS2 heterostructure photodetectors encapsulated in an ionic polymer are reported, which are uniquely able to operate at bandwidths up to 1.5 kHz whilst maintaining internal gain as large as 10 6 . Highly mobile ions and the nanometer‐scale Debye length of the ionic polymer are used to screen charge traps and tune the Fermi level of the graphene over an unprecedented range at the interface with WS2 . Responsivity R = 10 6 A W −1 and detectivity D* = 3.8 × 10 11 Jones are observed, approaching that of single‐photon counters. The combination of both high responsivity and fast response times makes these photodetectors suitable for video‐frame‐rate imaging applications. Abstract : High‐speed photodetection with an internal gain as large as 10 6 is realized for the first time in atomically thin heterostructures of WS2 and graphene. Highly mobile ions in the ionic‐polymer gate are used to screen charge traps enabling the creation of photodetectors suitable for video‐frame‐rate imaging applications.